PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Bagian Produksi PT. Karmand Mitra Andalan Surabaya) - Dewi Talli (FEB Universitas Lakidende, 2020)
This research aims to explain the effect of partial work motivation on employee performance, the effect of the work environment partially on employee performance, work motivation and the work environment simultaneously on employee performance. The study was an explanatory research with a quantitative approach, with 50 respondents using saturated sampling. Descriptive data analysis techniques with multiple linear regression analysis. Results showed that work motivation had a significant effect on employee performance with a t significance value of 0.000 smaller than Î± = 0.05 (0.000 < 0.05) with a regression coefficient of 0.636. The work environment had a significant impact on employee performance with a t significance value of 0.013 smaller than Î± = 0.05 (0.013 > 0.05) with a regression coefficient of 0.226. Work motivation and work environment simultaneously have a significant effect on employee performance with a significance value of F of 0.000 smaller than Î± = 0.05 (0.000 < 0.05) and able to contribute to a work performance variable of 0.660 or 66%. The remaining 34% were affected by other variables not studied in the study